Main principles of formation of air condition information model - Браиловский, H. H.; Моржов, C. B.; Хорошко, В. А. (Proceedings of National Aviation University (archive), 1999)
Formulated are the requirements to air condition model and on the ground of them models for different regimes are worked out: regular, special and mobile. Determined on the grounds of worked out models is a necessary set of radiotechnical means for provision of optimal and reliable air traffic control